Analysis Of Flow Process Of Employee Termination Dispute Resolution Settlement Based On Law No. 02 Year 2004 - Yuni Pratikno (Agregat: Jurnal Ekonomi dan Bisnis, 2019)
This study aims to determine the Termination of Work Relations Dispute Settlement according to Law No. 2 of 2004. This research uses descriptive qualitative research methods and library research with the approach of material / primary data, material / secondary data, and material / tertiary data. The results of the study state that if no agreement is reached, either party or party can file a lawsuit to the industrial relations court at the local district court where the worker or laborer works. The length of the mediation process is prolonged because many parties want to interfere in mediation.